The other Boleyn girl - Gregory, Philippa (London Harper Collins, 2002)
Mary Boleyn comes to the court of King Henry VIII, where she falls for the dashing king, and begins to enjoy her growing role as unofficial queen, however, she soon realizes she is merely a pawn in her family's ambitious plots as the king's interest begins to turn towards her best friend and rival, her sister, Anne. Text presented in Chinese.
"First published in Great Britain by HarperCollinsPublishers 2001"--Colophon.
Parallel title in simplified Chinese characters.
Translation of: The other Boleyn girl.
Adult
Adult
Text in simplified Chinese.
Keywords: Henry -- VIII, -- King of England, -- 1491-1547 -- Fiction; Henry -- VIII, -- King of England, -- 1491-1547 -- Fiction; Boleyn, Mary, -- 1508-1543 -- Fiction; Boleyn, Mary, -- 1508-1543 -- Fiction; Mistresses -- Fiction; Biographical fiction; Chinese language; Historical fiction; Mistresses -- Fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Great Britain -- History -- 1485-1603, Tudors -- Fiction; Biographical fiction; Historical fiction